Making friends and enemies on social media: the case of gun policy organizations. Issue 5 (12th September 2016) - Merry, Melissa
Abstract : Purpose: The purpose of this paper is to explore the role of interest groups in the formation of online echo chambers and to determine whether interest groups' use of social media contributes to political polarization. Design/methodology/approach: This study used a content analysis of nearly 10, 000 tweets (from 2009 to 2014) by the Brady campaign to Prevent Gun Violence and the National Rifle Association to examine how groups engage with their political allies and opponents. Findings: The results indicated that both groups engaged primarily with their supporters on Twitter while avoiding confrontation with their opponents. In particular, both groups used hashtags designed to reach their supporters, retweeted messages almost exclusively from other users with whom they agreed, and disproportionately used Twitter handles of their allies, while avoiding the use of Twitter handles of their opponents. Practical implications: The findings suggest that interest groups' use of social media accelerates the formation of online echo chambers, but does not lead to an increase in polarization beyond existing levels, given practices that maintain civility between opposing sides. Originality/value: This is one of few studies to examine the role of interest groups in the formation of online echo chambers. It also uses a novel approach – the examination of both the interactions that occur among social media users and those that are explicitly avoided.